Using political science to progress public health nutrition: A systematic review - Cullerton, K.; Donnet, T.; Lee, Andy; Gallegos, D. (Cambridge University Press, 2016)
© Copyright The Authors 2015. Objective Poor dietary intake is the most important behavioural risk factor affecting health globally. Despite this, there has been little investment in public health nutrition policy actions. Policy process theories from the field of political science can aid understanding why policy decisions have occurred and identify how to influence ongoing or future initiatives. The present review aims to examine public health nutrition policy literature and identify whether a policy process theory has been used to analyse the process. Design Electronic databases were searched systematically for studies examining policy making in public health nutrition in high-income, democratic countries. Setting International, national, state and local government jurisdictions within high-income, democratic countries. Subjects Individuals and organisations involved in the nutrition policy-making process. Results Sixty-three studies met the eligibility criteria, most were conducted in the USA and a majority focused on obesity. The analysis demonstrates an accelerating trend in the number of nutrition policy papers published annually and an increase in the diversity of nutrition topics examined. The use of policy process theory was observed from 2003; however, it was utilised by only 14 % of the reviewed papers. Conclusions There is limited research into the nutrition policy process in high-income countries. While there has been a small increase in the use of policy process theory from 2003, an opportunity to expand its use is evident. We suggest that nutrition po licy making would benefit from a pragmatic approach that ensures those trying to influence or understand the policy-making process are equipped with basic knowledge around these theories.